Guitar creativity of Agustin Barrios in the context of the development of Paraguayan music - Ivannikov, Tymur; Filatova, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The relevance of the article is the need to fill the shortage of research analytics, allowing to consider the composing and performing art of Agustín Barrios in the epicenter of the cultural context of the countries of the Latin American continent. Main objectives of the article is to study the creative heritage of the Paraguayan virtuoso, to reveal its influence on the formation and development of Latin American composing and performing guitar art. The methodology involves the use of historical, systemic, structural-functional methods (for a comprehensive analysis of historical events, studying of compositional, genre-stylistic and form-building elements of musical texture), comparative and phenomenological approaches (for comparing Latin American and European genre models, performing versions and extracting meaningful aspects of the studied works). The combination of these methods and approaches provides a wide panorama of the consideration of A. Barrios' creativity, in which major culturological generalizations are combined with genre-style and linguistic specificity of analytical material. Results and conclusions. Agustin Barrios' guitar art is one of the first bright pages of Latin American music of the twentieth century. Archival audio recordings of his performances have become part of the historical foundation. The expansion of the technical arsenal of guitar performance, the creation of a large array of new music, included in the concert and competitive programs of our days, serve as the facts of the undeniable achievements of the Paraguayan musician. He opened to the world the sound silhouettes of his musical culture, its historical heritage and new possibilities. As one of the spokesmen for the aesthetics of indigenismo, Agustín Barrios captured the ritual traditions and mythology of the Guaraní indigenous peoples in his guitar work, revealed the beauty of hybrid genre models in Indian, Spanish-Portuguese and African-American musical fusions. He introduced the academic foundations that go back to the origins of the genre memory of European art, and formed in a new way a lively rhythm-intonational flow of the folk Latin American song-dance tradition, bringing it to the world guitar concert-academic scene.